Making of a Teenage Service Class 2017
DOI: 10.1525/california/9780520292055.003.0006
|View full text |Cite
|
Sign up to set email alerts
|

The Making of a Teenage Service Class

Abstract: This chapter describes the complex and vacillating trajectory between higher education and low-wage work that defines the coming-of-age experiences of marginalized youth. Open access to certain institutions of higher education allow youth to postpone degrees indefinitely while claiming to be invested in college through isolated community college classes. This also reinforces the belief that social mobility through higher education is feasible. At the same time, emotional labor involved in the performance of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…This is particularly true for those who are in gangs, incarcerated, and/or in CPS (Abrams & Terry, 2017; Fader, 2013; Samuels & Pryce, 2008). Research from outside criminology on the transition to adulthood has suggested that the same is true even for economically and socially marginalized young adults who manage to stay out of gangs, drugs, and state custody (Ray, 2017; Silva, 2013). In criminology, however, a general focus on negative outcomes like gang membership, arrest, and incarceration precludes considerations of positive human development and the ways the state can help or hinder the process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly true for those who are in gangs, incarcerated, and/or in CPS (Abrams & Terry, 2017; Fader, 2013; Samuels & Pryce, 2008). Research from outside criminology on the transition to adulthood has suggested that the same is true even for economically and socially marginalized young adults who manage to stay out of gangs, drugs, and state custody (Ray, 2017; Silva, 2013). In criminology, however, a general focus on negative outcomes like gang membership, arrest, and incarceration precludes considerations of positive human development and the ways the state can help or hinder the process.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that familial poverty, low parental supervision and attachment, disrupted family structure, lower levels of parental education, familial criminality, sibling antisocial behavior, proviolent parental attitudes, and child maltreatment often characterize gang members’ backgrounds (Eitle et al, 2004; Hill et al, 1999; Thornberry et al, 1993; Thornberry et al, 2003). Contemporary research on family poverty and state intervention suggests that these familial risks extend far beyond youth traditionally considered to be at the “highest risk” of crime, victimization, and gang membership (Kim et al, 2017; Lash, 2017; Lee, 2016; Ray, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Against this discursive backdrop, participants developed a thick desire to refute stigmatizing depictions of their sexualities, and they acted on it by constructing themselves as being upwardly mobile via their college plans, which they understood as requiring them to be nonsexual. They learned that fulfilling their desire for upward mobility necessitated that they restrict their desire to explore their emerging sexuality, reflective of what April Burns and María Elena Torre (2004, 133) refer to as “anxious achievement,” resulting in a “reordering of the erotic, away from an erotics of the body as a site of pleasure and the self as sexually desiring, to an erotics of achievement and material success.” And in doing so, Latinas simultaneously distanced themselves from other young women in their community who have fallen into the “trap” of teen pregnancy (Garcia 2012; Ray 2017).…”
Section: Desiring To Refute Stigmatizing “Teen Mom” Discourses and Ex...mentioning
confidence: 99%
“…For one, the racial composition of the student body is a proxy for the racialized allocation of resources outside of schools, resources that shape students’ academic outcomes more than other characteristics of schools and teachers (Gamoran 2016; Hill 2016). The racial composition of the student body also corresponds to distinctive relationships with teachers (Solorzano and Ornelas 2004; Tyson and Roksa 2016) and distinctive peer contexts (Dance 2002; Ray 2018), with implications for individual students’ psychosocial outcomes (Butler-Barnes et al 2019; Riegle-Crumb and Morton 2017). We seek to understand how the racial composition of the student body differentiates the salience of ninth graders’ perceptions of their teacher as equitable for their math identity, among boys and girls of different races.…”
Section: School Racial Composition and The Salience Of Perceptions Of...mentioning
confidence: 99%